Effect of Presence/Absence of a Nasogastric Tube in the Same Person on Incidence of Aspiration - Fattal, Michael; Suiter, Debra M.; Warner, Heather L.; Leder, Steven B. (Otolaryngology–Head and Neck Surgery, 2011)
Objective. To determine what effect, if any, the presence or absence of a nasogastric (NG) tube in the same person had on the incidence of anterograde aspiration. Design. Case series with planned data collection. Setting. Large, urban, tertiary care teaching hospital. Subjects and Methods. Referred sample of 62 consecutively enrolled adult inpatients for fiber-optic endoscopic evaluation of swallowing (FEES). Group 1 (n = 21) had either small-bore (n = 13) or large-bore (n = 8) NG tubes already in place and had a FEES first with the NG tube in place and a second FEES after NG tube removal. Group 2 (n = 41) did not have an NG tube and had a FEES first without an NG tube and a second FEES after placement of a small-bore NG tube. Time between FEES was approximately 5 minutes. Patients were tested with thin liquid and puree food consistencies. Occurrence of aspiration for each consistency dependent on the presence or absence of an NG tube was recorded. Results. There were no significant differences (P > .05) in aspiration status for both liquid and puree consistencies in the same person dependent on presence or absence of either a small-bore or large-bore NG tube. Conclusions. Since objective swallowing evaluation (eg, FEES) can be performed with an NG tube in place, it is not necessary to remove an NG tube to evaluate for aspiration. Similarly, there is no contraindication to leaving an NG tube in place to supplement oral alimentation until nutritional requirements are achieved.
Keywords: dept.cmd; peer-reviewed

Initiating Safe Oral Feeding in Critically Ill Intensive Care and Step-Down Unit Patients Based on Passing a 3-Ounce (90 Milliliters) Water Swallow Challenge - Leder, Steven B.; Suiter, Debra M.; Warner, Heather L.; Kaplan, Lewis J. (Journal of Trauma and Acute Care Surgery, 2011)
Background: Pulmonary aspiration is a leading cause of nosocomial infection in the intensive care unit (ICU) and step-down unit (SDU). A key goal is to identify patients who exhibit increased aspiration risk before beginning oral alimentation. This study investigated the success of recommending specific oral diets to ICU and SDU patients based on passing a 3-oz water swallow challenge. Methods: A referral-based sample of 401 ICU and 92 SDU patients were prospectively analyzed. Amount of liquid and food ingested at the next day's meal 12 hours to 24 hours after passing a 3-oz challenge and specific diet recommendations were accessed electronically from oral intake information entered on each participant's daily care sheets. Drinking and eating success, clinically evident aspiration events, and accuracy of diet order recommendations were recorded. Care providers were blinded to the purpose of the study. Results: All 401 ICU and 92 SDU patients were successfully drinking thin liquids and eating 12 hours to 24 hours after passing a 3-oz challenge. Mean volume of liquid ingested at the next day's meal was 360 mL ± 181.2 mL for ICU and 356.4 mL ± 173.5 mL for SDU patients. Percent of meal eaten ranged from 10% to 100%. Patient care sheets indicated specific diet recommendations were followed with 100% accuracy. Conclusions: Successfully recommending specific oral diets for ICU and SDU patients based on passing a 3-oz water swallow challenge was supported. Importantly, when a simple bedside 3-oz challenge administered by a trained provider is passed, specific diet recommendations can be made safely and confidently without the need for further objective dysphagia testing.
Keywords: dept.cmd; peer-reviewed